Christian identity, piety, and politics in early modern England - Dodson, J. Michael (Reformation, 2023)
Keywords: book.review; dept.eng

Virginia Woolf, money, and “the world’s oldest profession” - Neverow, Vara (ITINERÁRIOS – Revista de Literatura, 2023)
Keywords: dept.eng

Oh So Yum! Inspiring Others to Explore the Many Flavors of Plant-Based Nutrition with Everyday Favorites and Weekend Fun Food: Volume 1: Non-Dairy Edition - Gibson, Lori Angelica (White Dove Cottage Industries, LLC, 2023)
Oh So Yum! Volume 1 is a little bit gourmet and a little bit every day. With recipes for non-dairy cheeses, savory entrees, sweet treats and so much more, there is something to satisfy every craving and the most discriminating palates.Whether you're new to plant-based nutrition or a seasoned veteran, you can continue to enjoy your favorite flavors while benefitting animals, the planet and your health. This book will show you how and will quickly become your most reached for resource for quick and easy, tasty and satisfying, crowd-pleasing meals.Praise for Oh So Yum!“Oh So Yum is not just the title of this wonderful book. It is exactly what this book is about—creating delicious and surprisingly easy foods that have all the taste and none of the regrets that often accompany tasty meals. The instructions are simple, and the results are spectacular.” - Neal D. Barnard, MD, FACCAdjunct Professor, George Washington University School of MedicinePresident, Physicians Committee for Responsible Medicine“Anyone who thinks plant-based eating means sacrificing foods you love, this book will quickly change your mind! Written from a clear place of passion—Lori has created the ultimate introduction and delicious guide full of many classic dishes and favorite desserts, plus lots of staple recipes to keep stocked in your fridge and use a thousand different ways!”- Natalie ThomasRecipe and Video Creator, Feasting on Fruit“Lori’s Feta cheese is FANTASTIC!!! She could start up a business selling vegan cheeses. I bet there are a lot of people looking for good alternatives – this one is the best!- Dawn Duval, Area Supervisor“Wow! Lori’s aged blue cheese is delicious. I was going to let it sit in the cellar to age a bit longer but couldn’t resist trying it with some marinated eggplant!!! Thank you again!!!!!!”- Cindy Schrank Kane, Maven of Moderation“The ricotta recipe turned out great! Very easy. I usually make a cashew ricotta but will be replacing it with this recipe because this tastes a lot more like real ricotta to me. I bet I could swap this for dairy ricotta in any stuffed/layered pasta recipe without my non-veg friends and family noticing. I made the red pepper-fennel pasta with it too and liked how easy it was to transform the ricotta into a creamy pasta sauce.”- Melissa McBerkowitz, Recipe Testing Team, USA“The gelato is absolutely delicious! I took a portion to my mother who is vegetarian and trying to reduce her dairy intake and she said if she could buy vegan ice cream like this in the shops she would be very happy!”- Caroline Christian, Recipe Testing Team, UKWhat’s inside: 50+ whole food plant-based recipes including…Fresh, cultured and aged cheeses including feta, ricotta, mozzarella and cream cheese, plus REAL aged cheeses such as Camembert and Blue cheese.Veganized versions of popular dishes including stuffed shells, spanakopita (Greek Spinach Pie) and zucchini pad Thai.Dressings, sauces, appetizers and sides such as gourmet blue cheese dressing, marinated feta, mushroom antipasto, marinated eggplant and even potato salad.Weekend fun foods including smoked portobello CrunchWrap, jackfruit caritas and pizzeria style pizza.Fabulous desserts such as cheesecake, cashew cream parfaits, chocolate peanut butter pie and gelato.
Keywords: dept.eng

War in Travel Literature - Dubino, Jeanne; Kocabıyık, Orkun; Marino, Elisabetta; Smyth, Andrew J. (Cambridge Scholars Publishing, 2023)
These twelve chapters show how war functions as a subject, theme, impetus--willing and not--and backdrop in travel writing. Literature about travel and war in tandem enables readers to rethink both categories. The forms of travel writing about war addressed in this collection, including cookbooks and military magazines along with nonfiction narrative and memoir, reveal how heterogenous travel writing can be. To study travel in connection with war expands readers' understanding of the multiple motivations instigating travellers' journeys. War is about more than fighting on a battlefield; its reach is extensive, encompassing the spheres surrounding its battlefields and fronts. The many actors involved in any conflict attests to the ways war is absorbed into their worlds, permeates their thoughts and spurs their actions. Readers interested in travel literature from the beginning of the nineteenth century through the present day will find this volume to be of especial interest.
Keywords: dept.eng

Chronic: A Memoir - Dimyan, Rebecca (Woodhall Press, 2023)
In this powerful debut, Rebecca Dimyan details her experience with endometriosis, a chronic disease which effects one in ten women worldwide. This painful condition takes an average of seven years to be diagnosed and has no proven cure. Most women will undergo multiple surgeries, take countless painkillers and other drugs, and will still endure regular pain and other complications. With honesty, vulnerability, and sometimes humor, Dimyan explores the ways the condition has impacted her experiences, her body, her pain, and her joy. She takes her audience on an emotional journey through her teenage years, early twenties, and into her thirties as she becomes a professional woman, wife, and mother. Dimyan blends research, anecdotes, and advice as she shares the relief she’s found through alternative treatments and holistic medicine. Chronic isn’t just a story about one woman’s illness—it is a memoir about all the pain, pleasure, heartbreak, friendship, love, and hope she experiences on her path to healing.
Keywords: dept.eng

Lessons for My Daughters (Taught to Me by bell) - Hutchinson, Brandon L. A. (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
As a tenured professor at a predominantly white institution (PWI), I am aware of the hardships we face in the academy; as a mother of three Black girls, a wife to a Black man, I am full. And yet, I must make space to see my own self clearly. Each day as a Black woman, I must set the intention to save my own life.
Keywords: Identity; Introspection; Self-care; dept.eng

My Face-Eating Octopus - Furey, Rachel (Harpur Palate, 2023)
Keywords: dept.eng; literary-nonfiction